Can the Cadillac Tax Be Made Less Regressive by Replacing It with an Exclusion Cap? Methods and Results - White, Chapin (RAND Corporation, 2015)
The Affordable Care Act's "Cadillac tax" consists of a 40-percent excise tax on premiums for employer-sponsored health plans in excess of a dollar limit. This report uses RAND's COMPARE microsimulation model to compare the effects of the Cadillac tax versus an alternative tax, based on an exclusion gap, on families in different income ranges.